Doors (Friedman/Fairfax Publishers)
1 online resource
Keywords: "In Doors: History, Repair and Conservation, readers are guided through the function, history, development, care, repair and conservation of doors by chapter authors who are experts in their field. This book offers depth and range of detail from dating and archaeology right through to the surveying, recording, engineering and curation of the door, its furniture and the part of the building into which it is set. Doors vary from basic designs to exceptional and intricate masterpieces of craftmanship. Whether wood, stone, metal or glass, throughout history doors have been vital barriers against weather and intruders, providing those inside with protection, privacy and comfort. Split into three sections, this book covers history, development, identification and dating of doors, maintenance and engineering of doors and door openings, and materials of doors, their furniture openings and surrounds. Throughout the book the authors provide detailed photographs, drawings, techniques and methodologies and the latest research available. Doors is the first major reference work devoted to the understanding of doors and doorways and the issues surrounding their repair and conservation. This comprehensive, highly illustrated, full-colour study will provide professionals, students, and academics with a complete overview of door conservation that will inform both research and practice for years to come"--